Legal Study For Land Conversion in the Green Open Space Policy (Cirebon Regency Case Study) - Nurlaelah, Nurlaelah; Kurniawati , Iis; Ramadhani , Raden Sudani; Sutrisno , Endang; Harmono , Harmono (PT FORMOSA CENDEKIA GLOBAL, 2025)
Land conversion is a crucial issue in spatial planning and environmental protection policies in Indonesia, especially in the context of providing Green Open Space. The Minister of ATR/BPN Number 14 of 2022 affirms the obligation of a minimum of 30% Green Open Space from the city area, which consists of 20% Public Green Open Space and 10% Private Green Open Space. Using normative and empirical juridical approach methods to examine the problem of land conversion and the effectiveness of spatial planning laws and state administration in controlling these phenomena. The analysis results show that despite the regulatory regulations, there are still weaknesses in supervision and law enforcement that cause the rampant illegal and unsustainable land conversion. For this reason, it is necessary to increase supervision, enforce strict laws, and strengthen policies and regulations related to green open spaces to ensure the sustainability of ecosystem functions and support sustainable development. This study provides strategic recommendations for policymakers, law enforcement, and the community regarding the enforcement of land conversion laws according to the principles of open space conservation. This article recommends strengthening the spatial-based surveillance system, consistently applying administrative sanctions, and involving the public in the spatial planning process.